ASSESSING THE IMPORTANCE AND SIGNIFICANCE OF PUBLIC-PRIVATE PARTNERSHIPS IN MANAGING TOURISM DEVELOPMENT - Mamayusupova Dilovarkhan Begmatovna (Galaxy International Interdisciplinary Research Journal, 2023)
In this scientific article, the role of public-private partnership (PPP) in managing the development of tourism activity is revealed, and the importance of this mechanism is evaluated using correlation-regression analysis.